2006
DOI: 10.1007/s10600-006-0256-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification by GC—MS of cymene isomers and 3,7,7-trimethylcyclohepta-1,3,5-triene in essential oils

Abstract: Retention indices of cymene isomers published in popular GC-MS atlases were found to be erroneous by analyzing synthetic samples. The following retention indices (RI) were found using a nonpolar phase (diphenyl:dimethylpolysiloxane, 5:95) for four essential-oil components with indistinguishable mass spectra: 3,7,3,, m-cymene (RI = 1022), p-cymene (RI = 1024), and o-cymene (RI = 1039). The relative distributions of these compounds were evaluated based on the analysis of about 1000 essential oils. Simple method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…The most frequently observed isomer is p-cymene. Data presented in Table 1 are largely based on the results of Collin et al, 41 and Romanenko et al 42 Note that the observed elution order is in agreement with the correlation between boiling points and elution order of isomers. It is known that for isomers of the same homologous series the elution order on nonpolar stationary phases corresponds to the order of their boiling points.…”
Section: Retention Data Presentation and Discussionsupporting
confidence: 72%
“…The most frequently observed isomer is p-cymene. Data presented in Table 1 are largely based on the results of Collin et al, 41 and Romanenko et al 42 Note that the observed elution order is in agreement with the correlation between boiling points and elution order of isomers. It is known that for isomers of the same homologous series the elution order on nonpolar stationary phases corresponds to the order of their boiling points.…”
Section: Retention Data Presentation and Discussionsupporting
confidence: 72%
“…However, upon heating of the reaction mixture at 60 °C the formation of a new species was observed by thin-layer chromatography (TLC) with the reaction reaching completion after 12 h. After quenching the reaction mixture with saturated aqueous ammonium chloride solution and performing an aqueous extraction (DCM/water) the crude product was isolated and purified by silica column chromatography (EtOAc/hexanes 5:95) to yield a colorless solid as the principle product. Analysis of this material by 1 H-NMR revealed that it was not consistent with the reported data for the desired product 2 [6]. Furthermore, HRMS analysis suggested a molecular formula of C20H28N2 implying that a pseudo-dimeric species had alternatively been obtained.…”
Section: Resultsmentioning
confidence: 58%
“…Most of essential oils isolated from coniferous twigs by steam distillation do not contain 3,7,7‐trimethylcyclohepta‐1,3,5‐triene which is typical minor component of volatile fractions prepared by distillation of resins [23] . The larch essential oil ( Larix sibirica ) is the exception, and 3,7,7‐trimethylcyclohepta‐1,3,5‐triene was found in all the samples studied ( Table 3).…”
Section: Resultsmentioning
confidence: 95%
“…Optical activity. Specific rotations ([α] D 23 ) of the essential oil samples vary within different limits (Table 1). For fir (Abies sibirica) and spruce (Picea obovata), the value of the variance is insignificant, As for larch and pine oils, the values of optical rotation vary strongly: from 0.0 to À 34 for Larix sibirica, from À 2.0 to + 17 for Pinus sibirica, and from À 6.7 to + 2.6 for Pinus sylvestris.…”
Section: Resultsmentioning
confidence: 99%